A educação popular para todos de uma cidade educadora (Natal, Rio Grande do Norte, 1957-1964) - Marques, Berenice Pinto (2015)
This work has as a research subject of popular education policies of the city of Natal, Rio Grande do Norte, in the years 1957 to 1964. It aims to identify and analyze popular education policies developed and implemented by the Municipality of Natal in these years. To get the historical data, we establish as a guiding reserch question the following: Which elaborated educational policies were implemented by the Municipality of Natal in the years 1957-1964? and took over as the method Evidential Paradigm as proposition in Pinheiro (2009). This is anchored in documentary sources of Educational Legislation at National, State and Municipal levels as well as in the newspapers Folha de Tarde and Jornal de Natal; in existing documents from the archives of the Historical and Geographical Institute of Rio Grande do Norte (IHGRN), the Municipal Public Archives of Natal; iconographic sources; interviews and academic publications. In addition to these sources, we were inspired by the works of Aristotles (2011), Hobbes (2009), Freire (2011), Góes (1980), Germano (1989), Cortez (2005) and Galvão (2004). This research allowed us to understand that policies of popular education of Natal (RN) were based on a democratic educational practice, supported on three pillars, namely: participation and involvement of Natal population; construction and reconstruction of teaching practices in prioritizing their action programs to mass literacy and the training of lay teachers; and the democratization of culture. This historical process made Natal on educating city.